Attackers and defenders: tumor buds and lymphocytes as morphological biomarkers in colorectal cancer. Issue 11 (November 2022) - Kus Öztürk, Sonay; Haddad, Tariq S.; Zlobec, Inti; Lugli, Alessandro; Nagtegaal, Iris D.
Abstract: Tumor budding (TB) and tumor-infiltrating lymphocytes (TILs) are significant components of the tumor microenvironment emerging as prognostic biomarkers of colorectal cancer (CRC). TB is defined as single cells or clusters of up to four cancer cells dissociated from the tumor body and invading the surrounding stroma. Growing evidence supports TB's attacker effect in pT1 CRC and stage II colon cancer as an indicator of lymph node metastasis and unfavorable survival, respectively. TILs, in contrast, represent the host's ability against tumor progression as a defender. The attacker-defender model is relevant in CRC diagnostics influencing patient management. In this review, we will discuss these morphological biomarkers, the underlying mechanisms and the interaction between them, and the application of these biomarkers in current clinical practice.